The Voice of the Law in Transition - A'yun, Rafiqa Qurrata (Indonesia Law Review, 2015)
It is no doubt that the law has a tight relation with the language. We can see how language works in law since it comes from the idea, being enacted, and enforced. That is why language has a significant role along the legal process. This article will review the book written by Ab Massier which assumes at least three aspect of linguistic job in law: doing law is acting by means of language into a lingual activity, which is based on texts, and is resulting in texts. The main issue in this book is based on the problems of Indonesian language of the law which has replaced the Dutch language. Massier criticize instrumental approach to language and the impact of Dutch in Indonesian law language. His analysis refers to James Boyd White's statement about a translation of authoritative texts as the primary feature to define law itself. It is the perspective of doing law as a lingual activity that consists of communicating, speaking, and writing. Almost all legal processes produce texts, and therefore the text means the authority of the law.